Main Analytical Methods for the Viability Assessment of Mesenchymal Stem Cells for Use as Cellular Medicines - Galocha-León, Cristina; Clares-Naveros, Beatriz; Gálvez-Martín, Patricia (Current Pharmaceutical Analysis, 2018)
Background: Mesenchymal Stem Cells (MSCs) are multipotent stem cells with therapeutic potential in advanced therapies and regenerative medicine. Currently, MSCs are being widely studied as cellular medicine. In the design and development of medicines with cells, the study of viability is an important quality control requirement. Objective: Description of the main analytical techniques to study the MSCs viability as cellular medicine. Results: The cellular medicine must contain viable cells, for its use in vivo the cell viability must be at least greater or equal to 80%. Therefore, the study of cell viability of MSCs during its ex vivo expansion and its final formulation is a prerequisite before being administered. Conclusion: In this review the main analytical techniques based on studies of the cell membrane integrity, morphological assays and fluorescence biosensors are described. All of them are approved for use in quality control programs for clinical use of MSCs.
Keywords: analytical methods